THE EFFECT OF SUPPLY AUTOMATION SYSTEMS TECHNICAL OPERATIONS READINESS OF INDONESIAN WARSHIP (CASE STUDY: DOPUSBEKTIM) - Antonius Fandiano (JOURNAL ASRO, 2019)
In the system of guiding material for the Navy the spare parts are supporting material because of their nature as a provision that supports the maintenance of the main material so that it is always maintained and maintained its quality. The Eastern Region Procurement Center Depot or Dopusbektim is the Technical Implementation Unit (UPT) of Head quarter of Indonesian Navy Service, which has the duty and responsibility to receive, store, maintain and distribute provisions to the user unit or user unit including of Indonesian Warship In especially those located in the Koarmatim region or currently is Second Fleet of Indonesian Navy (Koarmada II). In supporting its duties and functions as a storage and distribution facility, Dopusbektim has a structured and implemented supply pattern supported by an automated system that uses special applications so that the distribution process can be carried out better in supporting technical operations readiness of Indonesian Warship. However, in carrying out the Dopusbektim debriefing, it was felt that it was not optimal although it was supported by infrastructure because there were still obstacles and obstacles. This results in Dopusbektim's duties and functions, one of which is providing services in order to support technical operations readiness of Indonesian Warship has not been maximized. Therefore it is necessary to analyze which effects need to be improved in optimally supporting technical operations readiness of Indonesian Warship .Keywords: Supplies Pattern, Automation System, Indonesian Warship Technical Operational Readiness, Multiple Regression analysis.